Estrogen-Related Receptor α Directs Peroxisome Proliferator-Activated Receptor α Signaling in the Transcriptional Control of Energy Metabolism in Cardiac and Skeletal Muscle - Huss, Janice M. (American Society for Microbiology, 2004)
Estrogen-related receptors (ERRs) are orphan nuclear receptors activated by the transcriptional coactivator peroxisome proliferator-activated receptor γ (PPARγ) coactivator 1α (PGC-1α), a critical regulator of cellular energy metabolism. However, metabolic target genes downstream of ERRα have not been well defined. To identify ERRα-regulated pathways in tissues with high energy demand such as the heart, gene expression profiling was performed with primary neonatal cardiac myocytes overexpressing ERRα. ERRα upregulated a subset of PGC-1α target genes involved in multiple energy production pathways, including cellular fatty acid transport, mitochondrial and peroxisomal fatty acid oxidation, and mitochondrial respiration. These results were validated by independent analyses in cardiac myocytes, C(2)C(12) myotubes, and cardiac and skeletal muscle of ERRα(−/−) mice. Consistent with the gene expression results, ERRα increased myocyte lipid accumulation and fatty acid oxidation rates. Many of the genes regulated by ERRα are known targets for the nuclear receptor PPARα, and therefore, the interaction between these regulatory pathways was explored. ERRα activated PPARα gene expression via direct binding of ERRα to the PPARα gene promoter. Furthermore, in fibroblasts null for PPARα and ERRα, the ability of ERRα to activate several PPARα targets and to increase cellular fatty acid oxidation rates was abolished. PGC-1α was also shown to activate ERRα gene expression. We conclude that ERRα serves as a critical nodal point in the regulatory circuitry downstream of PGC-1α to direct the transcription of genes involved in mitochondrial energy-producing pathways in cardiac and skeletal muscle.